EMPOWERMENT EMPOWERMENT OF HOUSEWIVES IN EARLY DETECTION OF CHILDREN'S PULMONARY TB IN THE RW 8 AREA, PUTAT JAYA DISTRICT SURABAYA: - - Sari, Ethyca; M.Nancye, Pandeirot M.Nancye; Intiyaswati (Universitas Nahdlatul Ulama Surabaya, 2024)
Tuberculosis (TB) in Indonesia has been detected to be increasing in recent years. Community involvement in tackling TB disease is very necessary. Child TB cases are not clearly visible if the family does not understand the signs and symptoms they cause. There is a need for knowledge regarding early detection of pulmonary TB in children through TB ​​screening. In an effort to reduce the increase in children's TB, the participation of the family is needed, especially the mother who is currently the closest to the child. The aim of this community service is to increase the knowledge of housewives in early detection of TB disease in children. Community service activities include counseling, presentation of material, simulations and applying TB screening tests directly to children. This activity is carried out by 20 housewives from each RT, represented by 2 people. The activity lasts for 2 days. Empowerment and education through counseling proven to be able to increase the knowledge of housewives in carrying out TB screening in children in the area. It was found that the number screened was 152 children, consisting of cases without risk, 111 children, at risk/exposed: 26 people at risk, 15 people. It is hoped that this empowerment of housewives can continue optimally and sustainably so that the results of the discovery of suspected TB cases in children can be followed up by health workers at Community Health Centers in an effort to prevent and reduce the incidence of TB in children.